2017
DOI: 10.1186/s12879-017-2311-2
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine/dolutegravir dual therapy in HIV-infected, virologically suppressed patients

Abstract: BackgroundLittle is known about the applicability of dual treatments based on integrase inhibitors. We explored the combination of lamivudine + dolutegravir as an option when switching from standard cART in virologically suppressed patients.MethodsIn this prospective cohort we enrolled patients previously switched to 3TC + DTG who were 18 years or older, with no previous resistance mutations to the used drugs, having a HIV-RNA <50 copies/ml for 6 months or longer, negative for HBsAg and on a stable (>6 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 42 publications
(34 reference statements)
10
62
0
3
Order By: Relevance
“…Among the observational studies, the majority did not report detailed inclusion and exclusion criteria. Five observational studies reported virological outcomes at both time-points 12, 3033 . Amplification for drug resistance testing was successful for 19 of the 27 (70%) patients with VF.…”
Section: Resultsmentioning
confidence: 99%
“…Among the observational studies, the majority did not report detailed inclusion and exclusion criteria. Five observational studies reported virological outcomes at both time-points 12, 3033 . Amplification for drug resistance testing was successful for 19 of the 27 (70%) patients with VF.…”
Section: Resultsmentioning
confidence: 99%
“…However, dietary restrictions and drug interactions could represent a limit of the association of Rilpivirine + Dolutegravir. 3TC + DTG showed encouraging efficacy in previous switch studies , but these were limited by small sample sizes. In a randomized pilot study in virologically suppressed patients , 3TC + DTG was noninferior to standard three‐drug regimens, however, the study was limited by the small sample size and the strict inclusion criteria, and the 4% noninferiority margin indicated by the US Food and Drug Administration (FDA) for switch studies was not respected.…”
Section: Discussionmentioning
confidence: 99%
“…While simplification to DTG monotherapy has recently demonstrated suboptimal efficacy compared to triple ART , recent randomized trials have demonstrated the non‐inferiority to standard ART of the two‐drug regimens, DTG plus rilpivirine in virologically suppressed subjects and DTG plus lamivudine (3TC) in ART‐naïve patients . This latter combination has also showed promising results as a switching option in a non‐randomized trial and in observational studies , whereas a large randomized clinical trial exploring this strategy in now ongoing.…”
Section: Introductionmentioning
confidence: 99%